Pesticide application to agricultural fields: effects on the reproduction and avoidance behaviour of Folsomia candida and Eisenia andrei - Santos, M. J. G. (2019)
The objective of this work was to assess the impact of pesticide application to non-target soil organisms simulating what happens following pesticide application in agricultural fields and thus obtaining higher realism on results obtained. For that purpose, three commercial formulations containing the insecticides chlorpyrifos and endosulfan and the herbicide glyphosate were applied to a Mediterranean agricultural field. The soil was collected after spraying and dilution series were prepared with untreated soil to determine the impact of the pesticides on the avoidance behaviour and reproduction of the earthworm Eisenia andrei and the collembolan Folsomia candida. A significant avoidance was observed at the recommended field dose in case of endosulfan by earthworms (60 %) and in case of chlorpyrifos by collembolans (64 %). In addition, both insecticides affected the number of juveniles produced by the earthworms (EC(50) were below the recommended field dose). Glyphosate did not seem to affect either earthworms or collembolans in the recommended field dose. Folsomia candida was more sensitive to pesticide application than Eisenia andrei, what was corroborated by the EC(50) and LC(50) values. In conclusion, insecticides may affect the structure of the soil community by reducing the survival of collembolans and the reproductive capacity of collembolans and earthworms.